2019
DOI: 10.1021/acs.jpcc.9b00355
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Magnetic Properties of Cu-Containing Borates with “Antizeolite” Structure

Abstract: Crystals of copper-doped barium fluoride borate solid solutions Ba 3 (BO 3 ) 2−x F 3x :Cu were grown from hightemperature solution. Using X-ray single-crystal diffraction, the structure was solved and refined in Pbam space group. These crystals are colored in brown, revealing linear dichroism. Optical and electron spin resonance spectroscopic investigations concluded that the light absorption of Ba 3 (BO 3 ) 2−x F 3x :Cu crystals is caused by both the exciton and f ree charge carriers. This phenomenon is simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Earlier it was shown that OH – groups can substitute fluorine and oxygen anions in the structure of antizeolite borates, that is, OH – → F – , OH – + e – → O 2– . , We believe that the replacement of lithium in the [LiF 4 ] 3– groups with Cu 2+ is accompanied by the replacement of the four fluorine anions in the [LiF 4 ] 3– groups and the two nearest oxygen anions of the intrachannel [BO 3 ] 3– groups with OH – groups. These lead to the formation of [Cu­(OH) 6 ] 4– octahedral complexes in the structure.…”
Section: Results and Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Earlier it was shown that OH – groups can substitute fluorine and oxygen anions in the structure of antizeolite borates, that is, OH – → F – , OH – + e – → O 2– . , We believe that the replacement of lithium in the [LiF 4 ] 3– groups with Cu 2+ is accompanied by the replacement of the four fluorine anions in the [LiF 4 ] 3– groups and the two nearest oxygen anions of the intrachannel [BO 3 ] 3– groups with OH – groups. These lead to the formation of [Cu­(OH) 6 ] 4– octahedral complexes in the structure.…”
Section: Results and Discussionmentioning
confidence: 91%
“…The data of X-ray diffraction analysis show that copper ions in the structure of Ba 3 (BO 3 ) 2– x F 3 x :Cu with Pbam space group may occupy both flat distorted octahedral [CuF 6 ] 4– and rectangular [CuF 4 ] 3– coordination of 19 F atoms . For the space group P4 2 bc in which the [Ba 12 (BO 3 ) 6 [BO 3 ]­[LiF 4 ] crystallizes, copper may occupy three positions: a and b with symmetry C 2 and c with symmetry C 1 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently discovered new class of “antizeolite” borates have made a contribution to the diversity of the crystal chemistry of borates. They are built with a Ba 12 (BO 3 ) 6 6+ framework with channels along the c axis (Figure a), formed by altering barium-cube and anticube cages. In the case of the Ba 12 (BO 3 ) 6 [BO 3 ]­[BO 3 ] (Ba 3 B 2 O 6 ) “antizeolite”, which is a boron-enriched end member, both the anticubes and cubes are filled with disordered guest [BO 3 ] 3– groups (Figure b) .…”
Section: Introductionmentioning
confidence: 99%